A story of YHWH : cultural translation and subversive reception in Israelite history - Flynn, Shawn W. (Abingdon, Oxon ; New York, NY : Routledge, an imprint of the Taylor & Francis Group, 2019)
A Story of YHWH investigates the ancient Israelite expression of their deity, and tracks why variation occurred in that expression, from the early Iron Age to the Persian period. Through this text, readers will gain a better appreciation for the complexities and contexts in the development of YHWH, from its earliest origins to the Persian period. Two interpretive frameworks-cultural translation and subversive reception-are offered for filtering through the textual data and contexts. Comparative study with ancient Near Eastern deities and select biblical texts lead readers through early YHWHism, YHWH's original outsider status, and the eventual impact of urbanization on the expression. Perceived and real pressures then challenge urbanite YHWHism and invite new directions for forming a unique expression of divinity in the ancient world. This book is intended for those interested in the study of ancient divinity broadly as well as those who study ancient Israel and the Hebrew Bible. The work provides generalists with a better appreciation for the particular challenges in working in the ancient Near East and with the bible specifically, while it provides specialists with a broad theory that can be continually tested. For both, the study provides two reading lenses to work through similar questions and an accounting of why the many contextually driven and varied constructions of YHWH may have occurred.
OCLC-licensed vendor bibliographic record.
Keywords: God (Judaism) -- Name; Judaism -- History; HISTORY / Ancient / General